Efektivitas Terapi Empati Untuk Menurunkan Perilaku Bullying Pada Anak Usia Sekolah Dasar - Fatimatuzzahro, Adinar; Suseno, Miftahun Nimah; Irwanto (Petik: Jurnal Pendidikan Teknologi Informasi Dan Komunikasi, 2017)
empathy in primary school age children and to tackle issues of bullying behavior since basic education (elementary school) with empathy therapy. Subjects in this study were four students aged 10-12 years and had a propensity score bullying of moderate to high. The design was one group pre - test- post-test. Collecting data in this study was conducted using a scale of bullying behavior tendency with behavioral checklist model prepared by the researcher. Data analysis methods used by using techniques Wilcoxon Signed Rank Test to test for differences in the data score pre test, post test and post test2 (follow up). Results of the analysis score pre test-post test showed p value of 0.001 and post test2 (follow up) p value of 0.002. It can be concluded that the therapy empathy is effective in reducing the empathy bullying behavior in children of primary school age. Keywords — Therapy Empathy , Bullying Behavior